2016
DOI: 10.31234/osf.io/p25c2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wisdom, bias, and balance: Toward a process-sensitive measurement of wisdom-related cognition

Abstract: Philosophers and behavioral scientists refer to wisdom as unbiased reasoning that guides one toward balance of interests and promotes a good life. However, major instruments developed to test wisdom appear biased, and it is unclear whether they capture balance-related tendencies. We examined whether shifting from global, de-contextualized reports to state-level reports about concrete situations provides a less biased method to assess wise reasoning (e.g., intellectual humility, recognition of uncertainty and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(90 citation statements)
references
References 15 publications
1
89
0
Order By: Relevance
“…This function is highly situation-specific, which means that traditional wisdom research in psychology, which homes in on more global capacities, is mostly irrelevant to the derivation of a phronesis construct. A notable exception here, however, is the recent Situated WiseReasoning Scale, developed by Brienza, Kung, Santos, Bobocel, and Grossman (2017). The Situated Wise-Reasoning Scale operationalises the elements of wise reasoning, by shifting from global, decontextualised reports to state level reports about concrete situations (see also Grossmann, 2017).…”
Section: A Four-component Model Of Phronesismentioning
confidence: 99%
“…This function is highly situation-specific, which means that traditional wisdom research in psychology, which homes in on more global capacities, is mostly irrelevant to the derivation of a phronesis construct. A notable exception here, however, is the recent Situated WiseReasoning Scale, developed by Brienza, Kung, Santos, Bobocel, and Grossman (2017). The Situated Wise-Reasoning Scale operationalises the elements of wise reasoning, by shifting from global, decontextualised reports to state level reports about concrete situations (see also Grossmann, 2017).…”
Section: A Four-component Model Of Phronesismentioning
confidence: 99%
“…Past studies of wise reasoning suggest that the major components of wise reasoning depicted in Figure all load on a single latent factor (Brienza et al, ; Grossmann et al, ; Grossmann & Kross, ; Kunzmann & Baltes, ). However, it is possible that different situations may call for somewhat different components.…”
Section: Measuring Wise Reasoning and It's Relationship To Other Consmentioning
confidence: 96%
“…Further, wise reasoning is also associated with greater well‐being, as indicated by greater life satisfaction, emotional balance, and greater longevity (Grossmann et al, ; Grossmann, Gerlach, & Denissen, ), while intelligence showed little relationship to any of these outcomes (Grossmann et al, ). These findings suggest that while wise reasoning is associated with many individual difference measures, it involves some unique processes, with a unique nomological network not accounted by other existing measures (for a broader discussion of such relationships, see Brienza et al, ).…”
Section: Measuring Wise Reasoning and It's Relationship To Other Consmentioning
confidence: 96%
See 2 more Smart Citations